Upaya Meningkatkan Prestasi Belajar Peserta Didik dengan Menerapkan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) - Guslawati, Nia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This research aims to determine the effect of applying the cooperative learning model of NHT (Numbered Heads Together) on student motivation and learning outcomes in the subject of Islamic Religious Education (PAI) for class X students at SMA Negeri 1 Pagai Utara. This study was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The results of the study show a significant improvement in both motivation and learning outcomes in the second cycle compared to the first cycle. In cycle II, the average completion rate reached 93.33%, indicating that the NHT cooperative learning model can effectively improve student motivation and learning outcomes. The application of this model successfully created a more interactive and enjoyable learning environment, motivating students to actively participate in group discussions.